International Law : Cases and Materials with Australian Perspectives / [electronic resource] - Rothwell, Donald R.; Kaye, Stuart; Akhtarkhavari, Afshin; Davis, Ruth (Cambridge : Cambridge University Press, 2010)
With a strong focus on Australian practice and interpretation of international law, this comprehensive cases and materials textbook will provide students with a contemporary understanding of an area of law that has seen major changes in recent years. Written by a team of pre-eminent experts, International Law: Cases and Materials with Australian Perspectives is unique in reflecting the Australian context, perspectives and values on international law. Each chapter covers a substantive area of the law with specialist topics on human rights, law of the sea, and international environmental law. Students will be able to readily identify the key principles, rules and distinctive learning points and will benefit from the clear exposition of state practice in the field, how it has contributed to the development of the law, and how Australian governments have viewed and interpreted international law.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).